Application of WDXRF and EDXRF Spectrometry for Chemical Characterization in Oil Sludge using the Fundamental Parameter Algorithm - Aline Leone Muguet Pinto; Marcos Antonio Scapin; Alexandre Luiz de Souza; Cláudia Monteiro Paixão; Marycel Elena Barboza Cotrim; Sabine Neusatz Guilhen (Brazilian Journal of Radiation Sciences, 2025)
Oil sludge is a waste product generated by the oil industry, comprising organic substances (primarily long-chain polyaromatic, aromatic, and aliphatic hydrocarbons), inorganic compounds (such as sediments and metallic and non-metallic oxides), water, and oil processing residues. Radionuclides from the 238U and 232Th decay chains can be present in oil sludge, which justifies its classification as naturally occurring radioactive material (NORM). The oil industry produces approximately 60 million tons of oil sludge annually. Given the continuous generation of this waste, the development of additional storage sites will be necessary, incurring substantial costs. Furthermore, the storage and transportation of oil sludge pose significant environmental contamination risks. Due to its complex and heterogeneous composition, establishing a standardized methodology for classifying oil sludge presents considerable challenges. The development of an effective methodology for the analysis and classification of oil sludge is essential for proper waste management, as well as for facilitating the creation of treatment and reuse alternatives. X-ray fluorescence spectrometry (XRF) emerges as a promising analytical technique for classifying oil sludge, enabling direct, non-destructive analysis, thereby reducing both waste and analysis costs. In this study, wavelength dispersive X-ray fluorescence (WDXRF) and energy dispersive X-ray fluorescence (EDXRF) techniques were compared to assess their performance in analyzing the major (1–100%) and minor (0.01–0.99%) constituents in oil sludge samples. The elements were quantified using the Fundamental Parameters (FP) algorithm. The objective of this work is to develop a methodology for determining both major and minor elements in oil sludge, contributing to a more effective management of this waste.